Sexual Education in the Scope of Ethics: A Philosophical Study - Dian Aditya Suryani; Supriyanto (Konsultan Jurnal Ilmiah Indonesia, 2025)
Sex education is an important issue in the field of education that is not only related to biological aspects but also involves ethical dimensions, values, and human dignity. In practice, sex education is often understood in a narrow sense or trapped in an extreme dichotomy between permissive and repressive approaches, thus failing to fully develop students’ moral awareness. This article aims to examine sex education within an ethical framework through a philosophical approach as a more comprehensive and meaningful alternative. This study employs a qualitative library research method by critically reviewing literature on ethical philosophy, philosophy of education, sex education, as well as classical and contemporary Islamic ethical studies. Data analysis is conducted conceptually and reflectively by examining the ontological, epistemological, and axiological dimensions of sex education. The findings indicate that sex education, from a philosophical-ethical perspective, should be understood as a process of forming holistic human beings that emphasizes responsible freedom, respect for human dignity, and the internalization of moral values. Furthermore, sex education plays a significant role as a means of developing students’ moral awareness in understanding and managing sexuality wisely. Therefore, the philosophical-ethical approach provides a conceptual foundation for formulating sex education that is not merely informative but also oriented toward moral and humanistic development.